Problem based management in delayed presented burned in dr. Cipto Mangunkusumo General Hospital, Jakarta - Moenadjat, Yefta; Mulya, Dina (The New Ropanasuri Journal of Surgery, 2017)
Introduction. Burn injured victims managed in Burn Unit of dr. Cipto Mangunkusumo General Hospital, Jakarta (RSCM) is dominated by delayed presentation and categorized as the difficult cases. Though had been rescued before being referred to our unit, these cases were characterized by massive edema and minimal to nil responsiveness to standard burn fluid resuscitation and were followed by high mortality. Method. A retrospective study run on those resuscitated in period of 1998–2010 using different protocols aimed to find out the most suitable formula to treat these subjects. Pediatric–, chemical– and electrical burns was excluded. Hydration status, hemodynamic– and perfusion indices, complication(s), mortality as well as survival days were variables of interest subjected to statistical analysis. Significance met if p <0.05. Results. Out of 1768 subjects managed, 659 were enrolled in the study. Mortality in those treated in first period was 44.9% with survival 10.10 pbd ± 7.39, in the second period was 54.6% with survival 8.55 pbd ± 6.39, in the third period was 43.4% with survival 11.34 pbd ± 7.34, and the last period was 13.4% with survival 18.78 ± 6.32 pbd. Conclusion. In these characteristics, perfusion targeted resuscitation showed to be superior than volume oriented. Even though mortality remains the problem, survival days markedly increased.